Evaluating the Impact of ESG Performance on Corporate Financial Outcomes: An Empirical Analysis of the European Energy Sector - IFTIKHAR, ABDULLAH (My University, 2025)
This study examines the relationship between ESG disclosure and financial performance in European energy companies from 2014 to 2023, analyzing 860 firms with 3,691 firm-year observations. The findings reveal that while ESG disclosure shows no significant relationship with accounting performance (ROA), it has a significant negative correlation with market valuation (Tobin's Q). Individual component analysis demonstrates that social disclosure positively affects operational efficiency but negatively impacts market value, while environmental and governance disclosures show consistently negative relationships. Temporal analysis indicates that ESG effects on accounting performance fade after one year, but negative market reactions persist, suggesting structural investor skepticism toward sustainability investments in energy. These results highlight an ESG paradox where operational realities and market perceptions diverge. The study contributes to stakeholder theory by showing that ESG investments may not yield immediate financial benefits in capital intensive transitional industries and emphasizes the need for sector-specific approaches to sustainability in the energy sector.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance